CHATGPT AS A TOOL FOR ENGLISH ESSAY WRITING: PERCEPTIONS OF INDONESIAN EFL STUDENTS - Silalahi, Rentauli (elstic : english language linguistics culture, 2025)
ChatGPT has been widely used by university students for assignments, including writing English essays. This study aims to contribute to the literature on Indonesian students’ perceptions of ChatGPT’s ease of use and usefulness as an assistant for writing their English essays. Data was collected from 123 undergraduate students from IT and non-IT majors at a private university in Indonesia. The Technological Acceptance Model (TAM) was used to examine the students’ perceived ease of use and usefulness of ChatGPT 3.5 (free version) through closed-ended and open-ended survey questions. Descriptive analysis was employed to analyse the quantitative data, while thematic analysis was used for the qualitative data. Findings from the thematic analysis confirm those from the descriptive analysis, as both reveal that students find ChatGPT easy to use and helpful in generating ideas, finding resources, and addressing language issues. However, issues regarding ChatGPT’s limitations in understanding complex prompts, leading to inaccurate responses, were identified as a reason for caution when using the tool. This study indicates that ChatGPT has a positive impact on education, particularly for English as a Foreign Language (EFL) students, despite some concerns that should be well addressed, including work originality and over-reliance on the application.